Estudio epidemiológico retrospectivo de brucelosis canina y métodos de diagnóstico usados en algunos centros veterinarios en la ciudad de Bogotá (2019)
Canine brucellosis is a disease caused by the bacterium Brucella canis which is transmitted by contact with placental tissues, aborted fetuses, vaginal and seminal secretions from infected animals. The most important signs are abortion, epididymitis, orchitis and infertility problems. A good percentage of Colombian population lives in Bogotá D.C. and year after year its canine population also increase; this represents a risk factor for brucellosis transmission because it is a zoonotic disease